2012
DOI: 10.3844/ajassp.2012.1583.1593
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Adaptive Filter and Neuro-Fuzzy Filter in Artifacts Removal From Electroencephalogram Signal

Abstract: Problem statement:This study presents an effective method for removing mixed artifacts (EOG-Electro-ocular gram, ECG-Electrocardiogram, EMG-Electromyogram) from the EEGElectroencephalogram records. The noise sources increases the difficulty in analyzing the EEG and obtaining clinical information. EEG signals are multidimensional, non-stationary (i.e., statistical properties are not invariant in time), time domain biological signals, which are not reproducible. It is supposed to contain information about what i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 10 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…In the 1D signal, the various artifacts mixed with cannot be filtered directly because they pass through the body and turn into an interference component. Balaiah and Ilavennila (2012) found that EEG is subjected to noise signal and it is contaminated. Then the noise is removed by means of Adaptive filter and Neuro-fuzzy filter.…”
Section: Ajasmentioning
confidence: 99%
“…In the 1D signal, the various artifacts mixed with cannot be filtered directly because they pass through the body and turn into an interference component. Balaiah and Ilavennila (2012) found that EEG is subjected to noise signal and it is contaminated. Then the noise is removed by means of Adaptive filter and Neuro-fuzzy filter.…”
Section: Ajasmentioning
confidence: 99%
“…The BCI system (Fig. 1) has subsequent components: (i) a tool to record brain functionaries either invasive Electrocorticography (ECoG) [6] or non-invasive Electroencephalography (EEG) [7]; (ii) a preprocessor that minimizes the artifacts and noises [8]; (iii) a decoder which decodes the preprocessed signal into an impact signal [9] for (iv) an adscititious tool that might be a suitable application for the BCI (e.g., an automatic mechanism, a display monitor etc.) [10] [11].…”
Section: Introductionmentioning
confidence: 99%